«È bella la guerra! Evviva la guerra!»: Preziosilla reclutatrice nella Forza del destino (Gilgameš, 2016)
The «parte guerresca» («war component») in Verdi’s La forza del destino is described by the same author as «tutt’affatto episodica» («quite episodic»), although it is a constant presence in his production; nonetheless it gets its own important space during the opera. In particular one among the characters is defined almost exclusively in connection with war: that’s Preziosilla, whose only two appearances culminate into battle songs. In the second act she tunes a recruitment song – «Al suon del tamburo» («At the sound of drums») – with the meaningful refrain «è bella la guerra! evviva la guerra!» («how splendid is war! Hurrah for war!»), and in the third act a rataplan. The connection between a pretty gypsy girl and war neither is immediately comprehensible, nor is the relationship between her and the main plot of the drama: why Preziosilla, who all things considered is a secondary character, gets such an important space hinged on war? My purpose is to analyze this character, because of she reveals herself being very different from the topos of the operatic gypsy girl and has the fundamental task of introducing and integrating the conflict in the plot. In my paper I will examine the very persuasive way by which she introduces herself and that specific theme, focusing on her first entrance on stage: here she speaks strong words if we consider the particular political juncture in which the opera was composed, and raise people in order to persuade them to join the army of the Italian liberation war against Germans, «flagel d’Italia eterno e de’ figliuoli suoi» («the eternal scourge of Italy and of her sons»).